2003
DOI: 10.1002/j.2161-0045.2003.tb00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Persistence in Science and Engineering Career Aspirations

Abstract: The author investigated students' persistence regarding career aspirations in science and engineering (SE) professional careers as a function of race and sex. In a nationally representative sample of 8th graders, persistent racial minority and female students were compared with nonpersistent racial minority and male students regarding their self-concept, parental involvement, socioeconomic status, and academic achievement. Men were more likely than women to persist in SE career aspirations. Persistent students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
189
3
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(224 citation statements)
references
References 18 publications
17
189
3
7
Order By: Relevance
“…Prior work in STEM education suggests that when students have confidence in their abilities in STEM classes as well as positive attitudes toward STEM, they are more likely to be interested in and ultimately pursue and persist in STEM-related courses and careers e.g., [12,[69][70][71][72]. Bandura [73] found that students who reported higher math self-efficacy also reported greater intrinsic motivation, a finding reciprocated across STEM disciplines [64,74].…”
Section: Students' Beliefs About Ability Interest and Intrinsic Motimentioning
confidence: 99%
“…Prior work in STEM education suggests that when students have confidence in their abilities in STEM classes as well as positive attitudes toward STEM, they are more likely to be interested in and ultimately pursue and persist in STEM-related courses and careers e.g., [12,[69][70][71][72]. Bandura [73] found that students who reported higher math self-efficacy also reported greater intrinsic motivation, a finding reciprocated across STEM disciplines [64,74].…”
Section: Students' Beliefs About Ability Interest and Intrinsic Motimentioning
confidence: 99%
“…Attention centered on interactive and causal links between student background, educational and institutional commitment, and academic and social integration. These studies gave rise to validation analyses that focused on identifying constructs with the best set of complementary variables to maximize model explanation (Cabrera et al, 1992;Cabrera, Nora, & Castaneda, 1993;Braxton, Sullivan, and Johnson, 1997), while others concentrated on the impact of specific factors on retention, such as assimilation courses (Hendel, 2001;Sidle & McReynolds, 1999), selected program major (St. John et al 2004;Mau, 2003), admission status (Laden, Matranga, & Peltier, 1999), student ethnicity and gender (Grandy, 1998;Leppel, 2002), classroom-based learning experiences (Tinto, 1997;Braxton, Milem, & Sullivan, 2000), institutional support services (Lau, 2003), intention to leave (Okun, Benin, & Brandt-Williams, 1996), academic and social integration (Beil, Reisen, & Zea, 1999), and pre-collegiate academic preparation (Cambiano, Denny, & De Vore, 2000). Though most studies examine retention at the first-to-second year stage, when students typically depart, the growing use of survival analysis and event history modeling is expanding the focus of student retention beyond the freshmen year (Murtaugh, Burns, & Schuster, 1999;Ishitani & DesJardins, 2002;DesJardins, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly one reason for the success was that the participants were self-selected and quite ready to be persuaded that they had leadership and entrepreneurial talent. Another seems likely to be the nature of self-efficacy itself, a psychological characteristic known for its ability to have an enduring influence on related behaviour and interests (Mau 2003). Self-efficacy is known for its spiralling effect that, once well established, leads individuals to make choices and attempt tasks that reinforce and further increase the sense of confidence in one's capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…High and low levels of self-efficacy have serious consequences for an individual's belief in their ability to perform in a range of situations. High levels of self-efficacy have been linked to various behaviours such as innovation and opportunity recognition in entrepreneurship (Ardichvili et al 2003) and career persistence (Mau 2003).…”
Section: The Role Of Entrepreneurship Education In the Development Ofmentioning
confidence: 99%